Kajian Teologis Terhadap Penerapan Tradisi Masseroi Tondok Dalam Budaya Seko Di Desa Malimongan, Kecamatan Seko - Selan, Yunus; Hasmi, Hasmi; Manu, Charisal B.S.; Sahari, Gunar; Harti, Sri Dwi; Basongan, Citraningsih (STT Pelita Dunia, 2025)
This research examines the application of the Masseroi Tondok tradition in the culture of the Seko community in Malimongan Village, Seko District, through a theological approach. Masseroi Tondok, which means